High School English Teachers’ Perception of Critical Thinking Concepts in Writing Class - Diyah Herawati; Margana Margana; Anita Triastuti (Edulitics (Education, Literature, and Linguistics) Journal, 2025)
This study explores high school English teachers' perceptions of critical thinking and their integration into English writing instruction, focusing on the Indonesian context. Critical thinking is a cornerstone of education, yet its implementation in writing classes remains underexplored, especially in secondary education. This qualitative study employs a case study design involving five high school teachers. Data were collected through semi-structured interviews, classroom observations, and document analysis. The findings reveal that teachers conceptualize critical thinking as a combination of analytical skills, logical reasoning, and creative problem-solving. Strategies such as argumentative writing tasks, peer reviews, and open-ended questioning were employed to develop students' critical thinking in writing. However, challenges such as limited student readiness, time constraints, and insufficient resources impede effective implementation. The study further identifies contextual factors unique to the Indonesian educational setting, contributing to the broader understanding of critical thinking pedagogy in diverse environments. Implications suggest the need for professional development programs, curriculum reforms, and enhanced resource allocation to support critical thinking instruction. This research underscores the importance of integrating critical thinking into English writing curricula to equip students with essential skills for academic and real-world success. Future research should explore the longitudinal impacts of these strategies and their adaptability across different educational contexts.